Mata Najwa Talkshow And Satire Messages In the Episode "Waiting for the Terawan" - Eko Wahyudi; Nisa Afifah; Muchammad Rifki Maldini; Alifah Qonitah Imtinan; Susiana Uji Rahmawati; Mochammad Sinung Restendy (Journal of Communication Studies, 2022)
The development of television media in Indonesia is increasingly creative. This is inseparable from the problems faced by the country and its people. One of the interesting television programs to watch is a talk show that discusses current issues wrapped in formal or informal concepts. Formal are those who attend speakers or guest stars to discuss serious issues such as political disputes. While informal is a discussion that contains many elements of entertainment or jokes. However, from these two concepts, the Mata Najwa talk show program presents an educational and entertaining spectacle. The host, Najwa Shihab, asks smart questions and sometimes comes with comedy. The concept in the Mata Najwa program is also a means of connecting the voices of the Indonesian people, as is the issue of the health minister which is difficult to ask for clarification regarding the 2020 Covid-19 pandemic. The Mata Najwa program provides awareness with satire in the form of an empty seat interview in the episode "Waiting for Terawan", This inspires the people to realize how important the case is, as well as an insinuation to the government. The purpose of this study is to find out the satire messages contained in the process of interviewing the "empty seat" in the episode of mata najwa "waiting for the terawan". The method used is content analysis in order to conclude the results of the discussion in the form of interviews conducted at the najwa eye event, not imaginary. Keywords: Talkshow, Mata Najwa, Satire, Interview, Agenda Setting